(untitled) (ACME, 2015)
Since the 1990s the retrospective of Russian and East-European Early-Modern societies has largely benefited from several methodological turns. Objects and profiles of the past reinterpreted in cultural terms are emerging against the anthropological background. This trend does not proceed to better consent in the historical community; rather it reconciles them against Soviet interpretations of the past. In the times of the Russian Empire and Soviet Union the East-European Early-Modern period was conceptualized in terms of “growth”, understood as a strengthening of the rulership and concentration of territories under the power of monarchs – grand dukes, later tsars, of Moscow and kings of the “Jagiellonian Empire”.